New insights into the phenotypes of atopic dermatitis linked with allergies and asthma in children: An overview. Issue 8 (24th May 2018) - Amat, F.; Soria, A.; Tallon, P.; Bourgoin‐Heck, M.; Lambert, N.; Deschildre, A.; Just, J.
Summary: Atopic dermatitis (AD) is a complex disease with multiple causes and complex mechanistic pathways according to age of onset, severity of the illness, ethnic modifiers, response to therapy and triggers. A group of difficult‐to‐manage patients characterized by early‐onset AD and severe lifelong disease associated with allergic asthma and/or food allergy (FA) has been identified. In this study, we focus on these severe phenotypes, analysing their links with other atopic comorbidities, and taking into account the results from recent cohort studies and meta‐analyses. The main hypothesis that is currently proposed to explain the onset of allergic diseases is an epithelial barrier defect. Thus, the atopic march could correspond to an epithelial dysfunction, self‐sustained by a secondary allergenic sensitization, explaining the transition from AD to allergic asthma. Furthermore, AD severity seems to be a risk factor for associated FA. Results from population‐based, birth and patient cohorts show that early‐onset and severe AD, male gender, parental history of asthma, and early and multiple sensitizations are risk factors leading to the atopic march and the development of asthma. The importance of environmental factors should be recognized in these high‐risk children and prevention programs adapted accordingly. Effective targeted therapies to restore both barrier function and to control inflammation are necessary; early emollient therapy is an important approach to prevent AD in high‐risk children. Clinicians should also keep in mind the specific risk of atopic comorbidities in case of filaggrin loss‐of‐function mutations and the rare phenotypes of orphan syndromes due to heritable mutations in skin barrier components.